2020
DOI: 10.1155/2020/3049098
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Serum Metabolic Biomarkers of Diabetic Kidney Disease: A Widely Targeted Metabolomics Study

Abstract: Background and Objectives. Diabetic kidney disease is a leading cause of chronic kidney disease and end-stage renal disease across the world. Early identification of DKD is vitally important for the effective prevention and control of it. However, the available indicators are doubtful in the early diagnosis of DKD. This study is aimed at determining novel sensitive and specific biomarkers to distinguish DKD from their counterparts effectively based on the widely targeted metabolomics approach. Materials and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Interestingly, Han et al also reported changes in NEFAs and EFAs concentrations through different stages of DKD, which were hypothesized to be secondary to metabolic adjustment during kidney disease progression at the cost of end‐organ damage 86 . In the case‐control study previously described by Zhang et al, 69 it was reported that elevated concentrations of palmitic acid (C16:0), linolelaidic acid (C18:2N6T), linoleic acid (C18:2N6C), and lysophosphatidylcholine (20:4) in serum were associated with DKD onset. In support to this study, Li et al 89 used GC‐MS to analyze urine obtained from patients with type 2 diabetes with or without DKD and also detected that increased levels of both palmitic acid (C16:0) and stearic acid (C18:0) were related to DKD.…”
Section: Metabolomics Applied To the Diagnosis And Prognosis Of Dkdmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, Han et al also reported changes in NEFAs and EFAs concentrations through different stages of DKD, which were hypothesized to be secondary to metabolic adjustment during kidney disease progression at the cost of end‐organ damage 86 . In the case‐control study previously described by Zhang et al, 69 it was reported that elevated concentrations of palmitic acid (C16:0), linolelaidic acid (C18:2N6T), linoleic acid (C18:2N6C), and lysophosphatidylcholine (20:4) in serum were associated with DKD onset. In support to this study, Li et al 89 used GC‐MS to analyze urine obtained from patients with type 2 diabetes with or without DKD and also detected that increased levels of both palmitic acid (C16:0) and stearic acid (C18:0) were related to DKD.…”
Section: Metabolomics Applied To the Diagnosis And Prognosis Of Dkdmentioning
confidence: 97%
“…In fact, indoxyl sulfate, indole-3 acetic acid, and trimethylamine N-oxide are also known uremic toxins derived from protein metabolism by gut microbiota, and its high concentrations are associated with both DKD and cardiovascular disease. 67,68 In a case-control study, Zhang et al 69 analyzed the serum of 44 individuals with type 2 diabetes, 24 of those with DKD, and observed that trans-4-hydroxy-L-proline and 6-aminocaproic acid, a derivate of proline and derivative of lysine respectively, were associated with early DKD. In a nontargeted serum metabolomics study on 56 patients with DKD, Tavares et al 70 reported that norvaline and aspartate were inversely associated with the progress of DKD and risk of mortality.…”
Section: Amino Acidsmentioning
confidence: 99%
“…Proteomics and metabolomics have identified potential biomarkers to monitor DKD and its progression and provided information on disease pathophysiologic mechanisms. [79][80][81][82] More research on these 'multi-omics' methods will provide clinicians with the best approach to manage DKD in the future. Finally, bioinformatics have enabled the identification of noncoding RNA as potential biomarkers and therapeutic targets given their important role in DKD progression.⁸3 Investigating the regulatory network of these noncoding RNA will open a new outlook for understanding the molecular mechanisms in DKD and how the transcriptomes can act as novel biomarkers and potential therapeutic targets for DKD.⁸3 CONCLUSIONS DKD evolves from diabetic nephropathy, a critical microvascular complication of T1DM and T2DM.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…In recent years, numerous biomarkers have been proposed for the diagnosis of AKI, most of which are in development or validation stages (Wettersten and Weiss, 2013;Darshi et al, 2016;Zhang et al, 2020). Nevertheless, it is still unclear, whether the diagnosis of AKI requires a single biomarker approach or multiple biomarkers approaches, taking into consideration the complexity and multifactorial aspects of AKI (Baker, 2005;Abdelsattar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%